2018
DOI: 10.1159/000490903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucroferric Oxyhydroxide on Fibroblast Growth Factor 23 Levels in Hemodialysis Patients

Abstract: Objective: This study investigated the effects of sucroferric oxyhydroxide on fibroblast growth factor (FGF)-23 and dose reduction of erythropoiesis-stimulating agents (ESA) and intravenous saccharated ferric oxide in hemodialysis patients. Methods: In this prospective, open-label, parallel-group, multicenter trial involving patients receiving lanthanum carbonate hydrate, eligible patients were randomized to a sucroferric oxyhydroxide group or a control group. Hemoglobin, serum phosphate, FGF-23, iron, and fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The phosphate-lowering effect of sucroferric oxyhydroxide was maintained over 1 year of follow-up, and no iron overload was observed. In hemodialysis patients, sucroferric oxyhydroxide may lead to an increase in serum iron parameters, albeit to a much lesser extent than what is observed with ferric citrate 100, 101, 102…”
Section: Dietary Phosphate Restrictionmentioning
confidence: 90%
“…The phosphate-lowering effect of sucroferric oxyhydroxide was maintained over 1 year of follow-up, and no iron overload was observed. In hemodialysis patients, sucroferric oxyhydroxide may lead to an increase in serum iron parameters, albeit to a much lesser extent than what is observed with ferric citrate 100, 101, 102…”
Section: Dietary Phosphate Restrictionmentioning
confidence: 90%
“…Several studies have confirmed that iron-containing phosphate binders lower FGF23 in HD patients and that the ability of the agents to lower FGF23 levels may be independent of the effect of a decrease in phosphate [16][17][18][19]. In the present study, the changes in the levels of TSAT and phosphate were serially higher and lower in the oral iron group than those in the iv iron and non-iron treatment groups, respectively, and a high TSAT was an independent factor for decreased intact FGF23 levels.…”
Section: Discussionmentioning
confidence: 95%
“…To further investigate the effect of different phosphate binders on reducing serum intact FGF23 levels in patients with CKD, we performed a subgroup analysis (Figure 4). 6 studies used iron-based phosphate binders to treat patients with CKD (33,36,37,39,41,42), while 7 studies used noniron-based phosphate binders to treat patients with CKD (27,34,35,38,40,43,44). There was a significant statistical difference, indicating that the effect of ferric citrate on decreasing serum intact FGF23 levels was better than noiron phosphate binders (P<0.05).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…One was whether the patient's dietary phosphorus intake was restricted. There were 4 studies restricted patient's dietary phosphate intake (37,38,41,42), while 9 studies did not restrict patient's dietary phosphate intake during the treatment (27,(33)(34)(35)(36)39,40,43,44). The other was whether patients performed hemodialysis.…”
Section: Meta-regressionmentioning
confidence: 99%